Uso de palmiste en la alimentación de cerdos en la etapa de engorde. - Rodríguez Zambrano, Rodolfo Fabrizio (2012)
Research was conducted in the final stage of fattening pigs Palmiste in Landrace pigs - York, with an average age of 75 days. The experimental unit consisted of two animals with three treatments and four replications. Was performed on the property of Mr. Rodolfo Rodriguez, located at km 11 of the road the Mana - Latacunga Sector Progress to right margin, 2 km from the main, in the Canton La Maná - Cotopaxi Province. The duration was 60 days, and its objectives determine the weight gain in the three levels of palm kernel in feeding pigs in the fattening stage, determine the best level of palm kernel in feeding pigs in the fattening stage , establish the relationship of economic analysis study diets. We used a completely randomized design with three treatments and four replications. For comparison between means was used Tukey test, for the profitability of the treatments study reports the benefit - cost. The variables studied were total weight gain, total feed consumption, feed conversion total. In the variable weight gain did not show statistical difference between treatments, but numerically the biggest gain the kernel obtained 40% T3 (370.80 g day-1) and the lowest kernel Q1 profit 20% (306.5 g / day-1). In the variable feed intake was not obtained statistically significant difference, but there was still the largest numerical difference kernel T3 consumption 40% (216.8 g day-1) and lower power T1 20% kernel (1778.9 g / day-1). The variable feed conversion showed no statistically significant difference, but 20% T1 numerical kernel is the best converter with (6.7) and lowest in converting 40% T3 is the kernel with (7.4). In the variable production costs find the highest cost kernel in T2 30% ($ 372.07) and the lowest cost of registering the kernel T1 20% ($ 358.49). Found in net profit with the largest value the kernel T3 40% ($ 117.59) followed by 20% kernel T1 ($ 46.09) and the lowest recorded profit kernel T2 30% ($ 36.20).